x Turn on thread page Beta
 You are Here: Home >< Maths

# Factor theorum watch

1. 1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4.
Hence solve the equation x³+x²-4x-4=0

f(x) = x³ + x² - 4x - 4

f(x) = (x³ + x²) - (4x + 4)

f(x) = x²(x + 1) - 4(x + 1)

f(x) = (x + 1)(x² - 4)

f(x) = (x + 1)(x² - 2²)

f(x) = (x + 1)(x + 2)(x - 2)

x³ + x² - 4x - 4 = 0

(x + 1)(x + 2)(x - 2) = 0

Hi people I did start a thread yesterday on this, it seems the way I approached factor theorum yesterday was wrong so I've gone away and had a bash at it again can someone please let me know if I am now correct?
2. that's just factorising. the factor theorem is the remainder theorem and you sub in until you get 0. factorising like this is much better
3. (Original post by sunny1982)
..
4. Well you haven't actually used the factor theorem.

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: April 17, 2013
Today on TSR

### Negatives of studying at Oxbridge

What are the downsides?

Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams